New Rehabilitation Approaches for Upper Limb Function of Children With Hemiplegia - Seyed Mohammad Sadegh Hosseini; Hossein Sourtiji; Sahar Noorani Gharaborgha; Seyed Ali Hosseini (University of Social Welfare and Rehabilitation Sciences, 2017)
Objective Cerebral palsy is an example of a physical disorder that causes multiple impairments that affect function and physical performance. Hemiplegia is a physical impairment that can occur in childhood. One of the most disabling symptoms of hemiplegia is unilaterally impaired hand and arm function. Treatment options include physical therapy, occupational therapy, conductive education, neurodevelopmental therapy, peripheral splinting and casting, pharmacotherapy (e.g., botulinum toxin type A), and surgery. There is little evidence of successful treatment with any of these approaches. Thus, the study aimed at evaluating and determining the effective rehabilitation approaches on upper limb function of children with hemiplegia. Materials & Methods A literature review was carried out. All evidences that were located in the first, second and third levels of evidence based on evidence-based practice classification and have explored the effect of any form of forced use, constraint induced movement therapy, hand-arm bimanual intensive therapy, and traditional treatments were included in this review. Patients with hemiplegic cerebral palsy and aged between 0-19 years and the researches on the treatment of the upper limbs were included in the study. Results In this literature review, 19 articles were gathered from certain databases such as PubMed, Cochrane Library, Scopus, MeSH, and Index Medicus with key words like hemiplegic cerebral palsy, types of treatment approach, and upper limb dysfunction. Twelve articles in first level, six in second level, and one in third level were included in this study; most of these included articles were on the constraint-induced movement therapy. Conclusion Based on the positive results of all these studies, constraint-induced therapy, forced use and hand-arm bimanual intensive therapy seemed to show effectiveness as interventions to improve involved hand and arm function in children with hemiplegia. Nevertheless, we needed to conduct researches with level 1 of evidence for each of the above treatment methods, particularly hand-arm bimanual intensive therapy for use in medical centers. Forced use was started with animal studies and then was continued on human studies of stroke patients and eventually expanded to children with hemiplegic cerebral palsy. Further research based on principles of motor learning and neuroplasticity promoted the use of forced use and developed constraint-induced movement therapy. Finally, the hand-arm bimanual intensive therapy was developed to remove constraints and difficulties of intervention in constraint induced movement therapy. Each of these interventions may be useful for hemiplegia. Comparative studies between these interventions are suggested to study their effects on the target behaviors.